IDENTIFIKASI PROBLEMATIKA PENGEMBANGAN KURIKULUM PAI - Fadhli Rabbi, Mim; Alfiannur, Muhammad; Salamah, Salamah (CV. Lafadz Jaya, 2024)
The Islamic Religious Education (PAI) curriculum plays an important role in delivering students to achieve national education goals, namely forming Indonesian people who believe in and are devoted to God Almighty and have noble morals. However, along the way, PAI curriculum development is still faced with various problems. This research aims to identify the problems faced in developing the PAI curriculum. The research method used is qualitative with data collection techniques through literature study, observation and interviews. The research results show that there are several problems in the development of the PAI curriculum, namely: Lack of stakeholder involvement in the PAI curriculum development process. The use of technology in developing the PAI curriculum has not been optimal. Limited human resources who are competent in developing the PAI curriculum. Insufficient funds for developing the PAI curriculum. Lack of synchronization between the PAI curriculum and other subject curricula. Evaluation of the PAI curriculum has not been optimal. It is hoped that the findings of this research can provide input for related parties in developing a better quality and more sustainable PAI curriculum.